Coroleu, Alejandro (ed.) (2012). Lorenzo Valla «La falsa i inventada donació de Constantí» - Susanna Allés Torrent (Swervei de publicacions, 2012)
Coroleu, Alejandro (ed.) (2012). Lorenzo Valla La falsa i inventada donació de Constantí